2018
DOI: 10.1007/s11356-018-3064-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic biochar-based manganese oxide composite for enhanced fluoroquinolone antibiotic removal from water

Abstract: Magnetic biochar-based manganese oxide composite (MMB) and raw biochar (BC) were synthesized via pyrolysis at a temperature of 500 °C under anoxic conditions of potato stems and leaves, characterized, and successfully used for the removal of norfloxacin (NOR), ciprofloxacin (CIP), and enrofloxacin (ENR) as representative compounds of fluoroquinolone antibiotics (FQs). Characterization results suggested that FeO and MnO are the dominant crystals in MMB. MMB possessed large surface area and pore volume than BC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(25 citation statements)
references
References 41 publications
3
21
0
1
Order By: Relevance
“…Results showed that adsorption capacity of BC toward THPC reached up to 204 mg/g under optimized conditions, revealing the great potential and broad applicability in the wastewater treatment fields. Several research reports have also proved the excellent adsorption ability of BC in the removal of organic and inorganic contaminants from wastewater (Oladipo and Ifebajo 2018;Fan et al 2017;Li et al 2018b). The characteristics of BCs and use of different types of BCs for removing organic and inorganic contaminants from wastewater are reviewed and published by Inyang et al (2016), Mohan et al (2014) and Shaheen et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that adsorption capacity of BC toward THPC reached up to 204 mg/g under optimized conditions, revealing the great potential and broad applicability in the wastewater treatment fields. Several research reports have also proved the excellent adsorption ability of BC in the removal of organic and inorganic contaminants from wastewater (Oladipo and Ifebajo 2018;Fan et al 2017;Li et al 2018b). The characteristics of BCs and use of different types of BCs for removing organic and inorganic contaminants from wastewater are reviewed and published by Inyang et al (2016), Mohan et al (2014) and Shaheen et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…This is also the height at which conventional pollutants were removed the most quickly. 37 Moreover, the Fe-modied biochar exhibited a better adsorption capacity than the other matrix ller. Fig.…”
Section: Performance Of Different Cws At Removing Pollutantsmentioning
confidence: 97%
“…It was demonstrated that after three reuse cycles, BC-FeMn maintained almost 100% of the original adsorption capacity toward all the antibiotics tested [196].…”
Section: Biochar-metal Compositesmentioning
confidence: 98%
“…Composites derived from potato stems and leaves as well as from magnetic manganese oxide (BC-FeMn) were tested as adsorbents of three antibiotics belonging to the quinolone class, i.e., norfloxacin (NOR), ciprofloxacin (CIP), and enrofloxacin (ENR) [196]. Plant biomass including potato stems and leaves was impregnated with a solution of FeCl3•6H2O, and subsequently dried and impregnated with a solution of KMnO4 before pyrolysis.…”
Section: Biochar-metal Compositesmentioning
confidence: 99%